Work and non-work concerns and impact on healthcare workers during the COVID-19 first wave in Brunei Darussalam: Identifying key risk groups for targeted support - Ashish Trivedi; Alice Lai; Maria Fontelera; Regina Tan; Norzawani Ishak; Rizal Sablee; Kyaw N. Win (Journal of Public Health and Development, 2026)
Healthcare workers (HCWs) played an integral role as front-line essential workers during the COVID-19 pandemic. They were at high risk of COVID-19 transmission and faced psychological effects of fatigue and burnout, which ultimately influenced their participation and performance during the pandemic. This study was conducted to assess work and non-work concerns and the impact of COVID-19 on HCWs in Brunei Darussalam. A cross-sectional study using a web-based and self-administered questionnaire was conducted from July to August 2020, with 511 HCWs in Brunei Darussalam. Data were analysed for associations between demographic profile and perceived work, non-work concerns, and impact of the outbreak on the HCWs during the first wave of the COVID-19 pandemic. The risk of acquiring COVID-19 (79.8%) and the risk of transmission to family members (90.8%), friends (88.6%) and colleagues (87.2%) were the primary concerns reported by HCWs. Additionally, 62.8% reported being tasked with additional work duties, 59.2% experienced increased workload, 54.5% experienced feeling stressed, and 45.5% felt the effects of manpower shortages. Multivariate analysis showed higher work concerns among doctors (OR=2.29, CI:1.14-4.61), nurses (OR=2.47, CI:1.37-4.48), and those working in hospitals (OR=3.22, CI:1.54-6.73), health centres/clinics (OR=3.82, CI:1.78-8.18), and the National Isolation Centre (OR=6.16, CI:1.97-19.2). HCWs reporting stigma and discrimination had greater non-work concerns (OR=1.74, CI:1.09-2.79) and perceived impact (OR=4.57, CI:2.82-7.46). In conclusion, front-line HCWs, such as medical and nursing staff working in hospitals and health centres, reported higher work concerns compared to allied health professionals and support staff. The majority of HCWs experienced staff shortages, increased workload, and stress due to the demands of the pandemic. These findings highlight the need for targeted organisational and psychosocial support measures and increased awareness for frontline HCWs to improve their resilience during such health crises.